Peran Pembiayaan Murabahah di BMT Mandiri Sejahtera Cabang Sugio dalam Meningkatkan Pendapatan UMKM Pasar Sugio Lamongan
Small and medium micro enterprises (MSMEs) has the important role in the community for expanding employment and giving economic services that spread to the community, increasing business income and achieving benefit and prosperity among others. MSMEs basically need the support of micro finance institutions which provides the funding to raise the financial asset of MSME using sharia system. This study aims at answering the question about the role of mura>bah